Synthesis, Characterization and Antimicrobial Studies of Mn(II), Fe(III) and Co(II) Complexes of 2-cis-3,7-Dimethyl-2,6-Octadiene-1-Semicarbazone - CHAND, MANGAL; NAGAR, MEENA (Asian Journal of Chemistry, 2010)
Complexes of Mn(II), Fe(IIl) and Co(II) with 2-cis-3,7-dimethyl- 2,6-octadiene-1-semicarbazone fonned by condensation of semicarbazone hydrochloride and 2-cis-3,7-dimethyl-2,6-octadiene-1-al have been synthesized and their physico-chemical properties have been investigated by elemental analysis, magnetic measurements, molar conductance, electronic spectroscopy and infrared spectroscopy. The ligand was found to be bidentate chelating agent for the metal ions. All these complexes have been tested in vitro for their antimicrobial activity against bacteria Staphylococcus aureus (gram postitive) and Escherichia coli (gram negative) and fungi Candida albicans and Aspergillus niger.